Specifics of strategic development priorities of the Central Asian region (Journal of Oriental Studies, 2021)
The main feature of modern world economic development is global interdependence, which embraces and modifies political, economic, social and environmental conditions. The relevance of the study is due to insufficient research on the processes of transformation of the world economy and the participation in it of the countries of the Central Asian region (CAR). In this regard, the goal of the paper is to analyze the process of transformation of the world economy in the context of institutional globalization, institutional support of international economic interaction, cooperation within the framework of international financial institutions, which are an integral component of the development of the world economy; substantiate strategic priorities for the development of the CARs. The leading method to the study of this issue is the analysis method, which allows to comprehensively consider the strategic priorities of the development of the countries of the Central Asian region in the context of globalization. The paper presents the system of using double standards in the areas of international regulation, identifies obstacles to realizing the benefits of free trade, and reveals the factors of institutional transformation of international economic relations. The materials of the paper are of practical value for the further studying the prospects for the international competitiveness of the countries of the Central Asian region, which is able to develop on its own intellectual basis with the production of the latest scientific and technological solutions in the innovative segments of the world market and provide the proper conditions for the life of the nation.Key words: economy, international relations, globalization, development, world politics.